2021
DOI: 10.1155/2021/4088184
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Use Behavior of Knowledge Payment Platform Based on Edge Computing under Mobile Information System

Abstract: From 2015 to the end of 2016, the Internet set off a wave of payment for knowledge. Pay-for-knowledge platforms such as Fenda, iGet, and Qianliao went online quickly, and platforms such as Himalaya FM, Zhihu, and Qingting FM gathered to launch paid columns. The number of users increased rapidly, and payment for knowledge was considered to have reached the trend of development. This article aims to study the introduction of edge computing in the mobile information system into the existence and inevitability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, grade level, monthly consumption, and frequency of use influence perceived usefulness, perceived ease of use, and perceived enjoyment of knowledge products [16]. Huo and Li [7] found that information flow among study participants in online consultations follows the common characteristics of searching, questioning, solving, implementing, and sharing, and that demand for health information is the driving factor for knowledge reuse.…”
Section: Knowledge Providers and Demandersmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, grade level, monthly consumption, and frequency of use influence perceived usefulness, perceived ease of use, and perceived enjoyment of knowledge products [16]. Huo and Li [7] found that information flow among study participants in online consultations follows the common characteristics of searching, questioning, solving, implementing, and sharing, and that demand for health information is the driving factor for knowledge reuse.…”
Section: Knowledge Providers and Demandersmentioning
confidence: 99%
“…The information quality of knowledge product description is measured by three variables: completeness, vividness, and relevance [3,51,52]. The credibility of knowledge producer is measured by three dimensions: reputation, experience, and integrity [7,8,32,45]. In accordance with customers' different purchase motivations and usage experiences, this study classified products into two types, namely utilitarian and hedonic products, where utilitarian products are based on practical utility, while hedonic products are based on entertainment experiences [17,53].…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations